Building Physics From physical principles to international standards - Pinterić, Marko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This textbook provides thorough coverage of the most important building physics phenomena: heat transfer, moisture, sound/acoustics, and illumination.  Since the book is primarily aimed at engineers, it addresses professional issues with due pragmatism, and by including many practical examples and related ISO standards. Nevertheless, in order to guarantee full comprehension, it also explains the underlying physical principles and relates them to practical aspects in a simple and clear way. This is achieved with the aid of more than 100 figures and consistent cross-referencing of formulas and ideas. In addition, interrelationships between the different building physics phenomena are elucidated in a way that will enable readers to develop performance specifications that inform the design process. The book will primarily appeal to students of civil engineering and architecture, as well as to all practitioners in these areas who wish to broaden their fundamental understanding oftopics in building physics.
Introduction -- 1 Basics of thermodynamics -- 2 Heat transfer -- 3 Heat transfer in building components -- 4 Moisture in building components -- 5 Basics of waves -- 6 Sound propagation -- 7 Building acoustics -- 8 Illumination -- Appendix A -- Tables -- Bibliography -- Index.
Keywords: Buildings -- Environmental engineering; Physics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Acoustical engineering; Building Physics, HVAC; Applied and Technical Physics; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Acoustics